Improving the Skills of the Children of Central Singapadu Village through Balaganjur and Gong Kebyar Training | Meningkatkan Keterampilan Anak-Anak Desa Singapadu Tengah Melalui Pelatihan Balaganjur dan Gong Kebyar - I Wayan Ardinatha Yasa (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
Thematic Real Work Lecture (KKNT) is one of the programs from MBKM (Merdeka Belajar Kampus Merdeka). This KKNT activity is part of the campus extracurricular, which applies the principles of the Tri Dharma of higher education. In this case, KKNT is a bridge in practice that the author carries out in Singapadu Tengah Village, Gianyar Regency, as a partner to add experience to honing community skills and provide motivation and innovation in society in the field of arts, especially in the field of musical arts for generations of young people by forming, fostering crazy percussion on Gong Kebyar and Balaganjur. Balaganjur comes from the words